Digital Divide: How Do Home Internet Access and Parental Support Affect Student Outcomes? - Jing Lei; Jingye Zhou (MDPI AG, 2012)
This study examined the relationship between home Internet access/parental support and student outcomes. Survey data were collected from 1,576 middle school students in China. Data were analyzed using descriptive analysis, independent-samples T-test, and regression analysis. Results indicate that students who had home Internet access reported higher scores than those without home Internet on all three dimensions: Computer and Internet self-efficacy, Attitudes towards technology and Developmental outcomes. Home Internet access and parental support were significantly positively associated with technology self-efficacy, interest in technology, perceived importance of the Internet, and perceived impact of the Internet on learning. Findings from this study have significant implications for research and practice on how to narrow down the digital divide.